2018
DOI: 10.3892/etm.2018.6487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraperitoneal or intracerebroventricular injection of streptozotocin on learning and memory in mice

Abstract: Alteration of behavior and PSD proteins in cerebral cortex and hippocampal synaptosome in the Alzheimer's disease (AD) mouse model were determined. AD was established by intraperitoneal injection of streptozotocin (STZ) in neonatal mice (intraperitoneal AD group) or intracerebroventricular injection of STZ in adult mice (intracerebroventricular AD group). Body weight and blood sugar level were measured. Following Morris water maze (MWM) test and fear-conditioning test, cerebral cortex and hippocampus tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Loss of body weight is a common characteristic in AD patients and ICV-STZ rodents have also been shown to lose weight without experiencing any change in blood glucose [11]. In our study, CM-STZ caused weight loss during the injection period, which recovered to control An additional benefit of CM-STZ injection model is the ability to administer many injections over time, due to the reduced invasiveness of the procedure.…”
Section: Discussionsupporting
confidence: 49%
“…Loss of body weight is a common characteristic in AD patients and ICV-STZ rodents have also been shown to lose weight without experiencing any change in blood glucose [11]. In our study, CM-STZ caused weight loss during the injection period, which recovered to control An additional benefit of CM-STZ injection model is the ability to administer many injections over time, due to the reduced invasiveness of the procedure.…”
Section: Discussionsupporting
confidence: 49%
“…ICV-STZ has been shown to induce contextual memory deficits in mice (Zhang et al 2018). To assess the involvement of MIF in contextual memory deficits, we tested the behavior of the different experimental groups using the fear conditioning paradigm.…”
Section: Pharmacological Mif Inhibition In Icv-stz Mice Influences Spmentioning
confidence: 99%
“…The ICV-STZ mouse model is a non-transgenic mouse model mimicking some aspects of sporadic AD, including neuroinflammation, disruption of tau phosphorylation, insulin signaling, Aβ pathology and cognitive deficits (Nazem et al 2015;Grunblatt et al 2007;Salkovic-Petrisic et al 2006;Chen et al 2012;Grieb 2016;Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…STZ (intraperitoneal or intracerebroventricular injection) might cause insulin deficiency, as well as Aβ deposition, hyperphosphorylation of Tau protein, loss of neurons, and other AD pathologies in brain . Reeta et al injected STZ (3 mg·kg −1 ) into rats’ ventricle and found that the oxidative stress, acetylcholinesterase activity, and inflammatory cytokines have been increased both in hippocampus and cortex in rats.…”
Section: Metabolic Damage Modelsmentioning
confidence: 99%
“…STZ (intraperitoneal or intracerebroventricular injection) might cause insulin deficiency, as well as Aβ deposition, hyperphosphorylation of Tau protein, loss of neurons, and other AD pathologies in brain. [49][50][51][52][53][54][55] Reeta Amyloid-related 21 0 5 21 57 Cholesterol 2 0 1 0 3 Cholinergic system 3 4 5 18 30 Inflammation 14 0 3 8 25 Other neurotransmitters 16 1 1 19 37 Tau 11 0 1 4 16 Unknown 10 0 3 4 17 Other 39 0 6 13 58 et al injected STZ (3 mg·kg −1 ) into rats' ventricle and found that the oxidative stress, acetylcholinesterase activity, and inflammatory cytokines have been increased both in hippocampus and cortex in rats. As a result, cognitive defects were also observed on the 28th day post STZ injection.…”
Section: Streptozotocin-induced Ad Animal Modelmentioning
confidence: 99%